Radiation-proof concrete as well as preparation method and application thereof

By using polypyrrole nanocrystals, acrylamide and nickel-iron slag in concrete, the conductive pathway and organic-inorganic interpenetrating network structure are formed, and the problem that existing concrete is difficult to effectively protect neutron rays in high-radiation environments is solved. Achieve strong neutron ray protection and moderate self-weight.

CN119409457APending Publication Date: 2025-02-11GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486203.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When existing concrete faces a high-radiation environment, it is difficult to effectively protect neutron rays, and there are safety hazards or structural redundancy caused by increasing the thickness of the protective layer or using heavy water.

Method used

Using a radiation-proof concrete, its formula includes silicate cement, polypyrrole nanocrystals, acrylamide, steel slag and nickel-iron slag, it forms conductive pathways and organic-inorganic interpenetrating network structure through in-situ polymerization of acrylamide. Enhance the neutron ray reflection and absorption capacity of concrete.

Benefits of technology

It achieves the effect of strong neutron ray protection, high strength and moderate self-weight, and simplifies the preparation process and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098765400000031
    Figure BDA0005098765400000031
  • Figure BDA0005098765400000041
    Figure BDA0005098765400000041
  • Figure BDA0005098765400000051
    Figure BDA0005098765400000051
Patent Text Reader

Abstract

The invention discloses radiation-proof concrete as well as a preparation method and application thereof. The anti-radiation concrete provided by the invention comprises the following preparation raw materials in parts by mass: 100 parts of Portland cement; 0.1 part to 1 part of polypyrrole nanocrystal; 3 to 10 parts of acrylamide; 0.005 to 0.1 part of an initiator; 0.005 to 0.2 part of a cross-linking agent; 5 to 10 parts of steel slag; 8 to 20 parts of ferronickel slag; 160 to 200 parts of fine aggregate; 270 to 330 parts of coarse aggregate; 1 part to 3.5 parts of a water reducing agent; and 40 to 65 parts of water. The preparation method of the anti-radiation concrete is simple, and comprises the following steps: uniformly mixing all the components in batches, and forming and curing to obtain the anti-radiation concrete. The anti-radiation concrete disclosed by the invention has the advantages of strong neutron ray protection capability, high strength, moderate self weight and the like, the preparation method is simple, the raw materials are easy to obtain, and the anti-radiation concrete is suitable for large-scale industrial application in the field of radiation protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of radiation protection technology, and in particular to radiation-proof concrete and a preparation method and application thereof. Background Art

[0002] Concrete has the advantages of wide source of raw materials, low price, simple preparation process, good mechanical properties and good durability. It is currently the most widely used basic building material and it is foreseeable that it will be difficult to be replaced in the short term. In recent years, with the continuous development of society and economy, the service environment of buildings has become increasingly complex. For example, nuclear energy facilities and laboratories, radiotherapy sites, space exploration laboratories and other facilities have high radiation intensity and high risk of radiation leakage, which puts forward new requirements for the radiation protection performance of concrete, especially the neutron radiation protection performance.

[0003] In order to block the penetration of neutron rays and other substances into concrete, it is usually possible to increase the thickness of the concrete protective layer, increase the neutron reflection and absorption capacity of the concrete, and so on. However, due to the limitations of the construction scene, simply increasing the thickness of the concrete protective layer will excessively increase the structural redundancy on the one hand, and significantly compress the available space on the other hand, which is not an ideal method to improve the neutron ray protection capability. Studies have shown that optimizing the composition of concrete and the neutron ray protection capability using functional components is a more effective method. Heavy water is a good neutron reflector. Directly used in the preparation of concrete can effectively increase the reflection of concrete to neutrons, but heavy water has potential harm to the human body. The use of low-grade iron ore and other metal ores can also help enhance the reflection of concrete to neutrons, but it often requires a large amount of addition to achieve a good effect, and the addition of a large amount of metal ores will cause the weight of the concrete to increase significantly. Metals such as boron and nickel have a high neutron capture cross section and high neutron absorption efficiency. They can be used in concrete to effectively increase its reflection to neutrons, but due to the large density difference between these metal materials and concrete, direct introduction into concrete is prone to the problem of metal powder sedimentation, and there is also the problem of weak interface bonding between metals and hydration products.

[0004] Therefore, it is of great significance to develop a concrete with strong neutron ray protection ability, high strength and moderate deadweight. Summary of the invention

[0005] The purpose of the present invention is to provide a radiation-proof concrete and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A radiation-proof concrete comprising the following raw materials in parts by weight:

[0008] Portland cement: 100 parts;

[0009] Polypyrrole nanocrystals: 0.1 to 1 part;

[0010] Acrylamide: 3 to 10 parts;

[0011] Initiator: 0.005 to 0.1 parts;

[0012] Cross-linking agent: 0.005 to 0.2 parts;

[0013] Steel slag: 5 to 10 parts;

[0014] Ferronickel slag: 8 to 20 parts;

[0015] Fine aggregate: 160 to 200 parts;

[0016] Coarse aggregate: 270-330 parts;

[0017] Water reducing agent: 1 to 3.5 parts;

[0018] Water: 40 to 65 parts.

[0019] Preferably, the particle size of the polypyrrole nanocrystals is 20 nm to 100 nm.

[0020] Preferably, the initiator is at least one of ammonium persulfate and sodium persulfate.

[0021] Preferably, the cross-linking agent is at least one of N,N'-methylenebisacrylamide, sodium vinyl sulfonate and acrylic acid.

[0022] Preferably, the particle size of the steel slag is 10 μm to 20 μm.

[0023] Preferably, the particle size of the nickel-ferronickel slag is 15 μm to 40 μm.

[0024] Preferably, the fine aggregate is at least one of natural river sand and machine-made sand, and has a particle size of 0.075 mm to 4.75 mm.

[0025] Preferably, the coarse aggregate is at least one of granite, diabase and limestone, and has a particle size of 4.75 mm to 26 mm.

[0026] Preferably, the water reducer is a polycarboxylate water reducer.

[0027] A method for preparing the radiation-proof concrete as described above comprises the following steps:

[0028] 1) dispersing polypyrrole nanocrystals, acrylamide, a crosslinking agent and a water reducing agent in a portion of water to prepare a polypyrrole-acrylamide mixed solution, and mixing silicate cement, steel slag, nickel-iron slag, fine aggregate and coarse aggregate to prepare a dry mix;

[0029] 2) Disperse the dry mix and the initiator in a portion of the water, add the polypyrrole-acrylamide mixed solution and the remaining water, mix well, and then perform molding and curing to obtain radiation-proof concrete.

[0030] Preferably, the specific operation of the curing in step 2) includes: first curing at 40°C to 50°C for 3h to 8h, and then transferring to a room temperature environment for curing until the total curing time reaches 25 days to 30 days.

[0031] A building material comprising the radiation-proof concrete.

[0032] Principle of the present invention: The present invention utilizes acrylamide to carry out in-situ polymerization in concrete, which can ensure uniform dispersion of polypyrrole nanocrystals on the one hand, thereby forming a conductive path through the polyacrylamide network, which is helpful for the reflection of rays, and on the other hand, it can also utilize the synchronous formation of polyacrylamide and hydration products to construct an organic-inorganic interpenetrating network structure, thereby enhancing the toughness or crack resistance of concrete. The polyacrylamide polymer network contains abundant hydroxyl groups, which helps to significantly improve the number density of protons in concrete, and thus can efficiently capture neutrons. Grinding steel slag to a particle size of 10μm to 20μm can effectively improve its hydration activity, avoid the risk of cracking caused by delayed hydration of steel slag, and make full use of the iron-containing phase therein to increase the conductivity of concrete. Nickel-iron slag can not only provide physical filling and promote the development of early strength of concrete, but also improve the conductivity of concrete and directly improve the capture efficiency of concrete for neutrons through the nickel-containing alloy therein.

[0033] The beneficial effects of the present invention are as follows: the radiation-proof concrete of the present invention has the advantages of strong neutron ray protection capability, high strength, moderate deadweight, etc., and its preparation method is simple and the raw materials are easy to obtain, and it is suitable for large-scale industrial application in the field of radiation protection.

[0034] Specifically:

[0035] 1) The amount of the nano-component (polypyrrole nanocrystal) in the radiation-proof concrete of the present invention is small, and the nano-component is evenly dispersed in the concrete by means of acrylamide;

[0036] 2) The radiation-proof concrete of the present invention contains polypyrrole nanocrystals, steel slag and nickel-iron slag, and realizes multi-scale conductive phase distribution by means of the formation of a polyacrylamide polymer network, thereby increasing the conductivity of the concrete and further improving the neutron ray protection capability of the concrete;

[0037] 3) The polyacrylamide in the radiation-proof concrete of the present invention can provide a large amount of hydroxyl groups and make full use of the iron-containing minerals in the steel slag and the nickel-iron alloy of the nickel-iron slag, directly improving the neutron capture ability of the concrete, thereby improving the protection ability against neutron rays;

[0038] 4) The 28-day neutron attenuation coefficient of the radiation-proof concrete of the present invention is 0.07 cm -1 ~0.30cm -1 , the 28-day compressive strength is 45MPa~60MPa, the 28-day dynamic elastic modulus is 25GPa~42GPa, the 28-day shrinkage rate is 110μm / m~180μm / m, the neutron ray protection ability is strong and the strength is high;

[0039] 5) The preparation method of the radiation-proof concrete of the present invention is simple, the raw materials are easy to obtain, and it is suitable for large-scale industrial application in the field of radiation protection. DETAILED DESCRIPTION

[0040] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0041] Embodiment 1:

[0042] A radiation-proof concrete, the raw material composition of which is shown in the following table:

[0043] Table 1: Raw material composition of a radiation-proof concrete

[0044]

[0045]

[0046] The preparation method of the above-mentioned radiation-proof concrete is as follows:

[0047] 1) dispersing a polycarboxylate water reducer in 10 parts by mass of water, adding polypyrrole nanocrystals, and ultrasonically dispersing for 20 minutes, adding acrylamide, and ultrasonically dispersing for 30 minutes, and then adding N,N'-methylenebisacrylamide, and ultrasonically dispersing for 1 minute to prepare a polypyrrole-acrylamide mixed solution, and dry-mixing fine aggregate and coarse aggregate for 3 minutes, and then adding silicate cement, steel slag and nickel-iron slag and dry-mixing for 4 minutes to prepare a dry mix;

[0048] 2) Dispersing ammonium persulfate in 20 parts by mass of water, adding the dry mix, stirring for 4 minutes, adding the polypyrrole-acrylamide mixed solution and 20 parts by mass of water, stirring for 2 minutes, injecting into a mold for molding, and then curing at 40° C. for 5 hours, and then transferring to a room temperature environment for curing until the total curing time reaches 28 days, thereby obtaining radiation-proof concrete.

[0049] After testing, the 28-day neutron attenuation coefficient of the radiation-proof concrete in this embodiment is 0.27 cm -1 The 28-day compressive strength is 58MPa, the 28-day dynamic elastic modulus is 40GPa, and the 28-day shrinkage rate is 110μm / m, indicating that it has strong neutron radiation protection ability and high strength.

[0050] Note:

[0051] Neutron attenuation coefficient: using 241 An Am-Be radiation source (energy of 14.1 MeV) was used to irradiate a radiation-proof concrete sample (size of 10 cm × 10 cm × 10 cm), and a signal receiver was used to test the intensity of neutrons penetrating the concrete sample. The centers of the neutron radiation source, sample, and receiver were at the same height, the distance between the receiver and the sample was 15 cm, and the distance between the neutron radiation source and the sample was 200 cm. The neutron attenuation coefficient was calculated according to the following formula: Where μ is the neutron attenuation coefficient, x is the thickness of the concrete sample, I is the intensity of the neutron penetrating the concrete sample, and I0 is the intensity of the neutron before incidence.

[0052] Compressive strength: Tested in accordance with "GB / T 50081-2019 Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0053] Dynamic elastic modulus and shrinkage rate: Tested in accordance with "GB / T 50082-2009 Standard for Test Methods for Long-term Properties and Durability of Concrete".

[0054] Embodiment 2:

[0055] A radiation-proof concrete, the raw material composition of which is shown in the following table:

[0056] Table 2: Raw material composition of a radiation-proof concrete

[0057]

[0058] The preparation method of the above-mentioned radiation-proof concrete is as follows:

[0059] 1) dispersing a polycarboxylate water reducer in 13 parts by mass of water, adding polypyrrole nanocrystals, and ultrasonically dispersing for 30 minutes, adding acrylamide, and ultrasonically dispersing for 30 minutes, and then adding sodium vinyl sulfonate, and ultrasonically dispersing for 3 minutes to prepare a polypyrrole-acrylamide mixed solution, and dry-mixing fine aggregate and coarse aggregate for 4 minutes, and then adding silicate cement, steel slag and nickel-iron slag and dry-mixing for 4 minutes to prepare a dry mix;

[0060] 2) Sodium persulfate was dispersed in 26 parts by mass of water, and then the dry mix was added and stirred for 4 minutes, and then the polypyrrole-acrylamide mixed solution and 26 parts by mass of water were added and stirred for 2 minutes, and then injected into the mold for molding, and then placed at 40° C. for curing for 8 hours, and then transferred to a room temperature environment for curing until the total curing time reached 28 days, and radiation-proof concrete was obtained.

[0061] After testing, the 28-day neutron attenuation coefficient of the radiation-proof concrete in this embodiment is 0.15 cm -1The compressive strength after 28 days is 50MPa, the dynamic elastic modulus after 28 days is 32GPa, and the shrinkage rate after 28 days is 150μm / m, indicating that it has strong neutron radiation protection ability and high strength.

[0062] Embodiment 3:

[0063] A radiation-proof concrete, the raw material composition of which is shown in the following table:

[0064] Table 3 Raw material composition of a radiation-proof concrete

[0065]

[0066] The preparation method of the above-mentioned radiation-proof concrete is as follows:

[0067] 1) dispersing a polycarboxylate water reducer in 9 parts by mass of water, adding polypyrrole nanocrystals, and ultrasonically dispersing for 20 minutes, adding acrylamide, and ultrasonically dispersing for 10 minutes, and then adding acrylic acid, and ultrasonically dispersing for 2 minutes to prepare a polypyrrole-acrylamide mixed solution, and dry-mixing fine aggregate and coarse aggregate for 2 minutes, and then adding silicate cement, steel slag and nickel-iron slag and dry-mixing for 1 minute to prepare a dry mix;

[0068] 2) Dispersing ammonium persulfate in 18 parts by mass of water, adding the dry mix, stirring for 2 minutes, adding the polypyrrole-acrylamide mixed solution and 18 parts by mass of water, stirring for 1 minute, injecting into a mold for molding, and then curing at 40° C. for 3 hours, and then transferring to a room temperature environment for curing until the total curing time reaches 28 days, thereby obtaining radiation-proof concrete.

[0069] After testing, the 28-day neutron attenuation coefficient of the radiation-proof concrete in this embodiment is 0.10 cm -1 The compressive strength after 28 days is 45MPa, the dynamic elastic modulus after 28 days is 25GPa, and the shrinkage rate after 28 days is 180μm / m, indicating that it has strong neutron radiation protection ability and high strength.

[0070] Embodiment 4:

[0071] A radiation-proof concrete, the raw material composition of which is shown in the following table:

[0072] Table 4: Raw material composition of a radiation-proof concrete

[0073]

[0074] The preparation method of the above-mentioned radiation-proof concrete is as follows:

[0075] 1) dispersing a polycarboxylate water reducer in 12 parts by mass of water, adding polypyrrole nanocrystals, and ultrasonically dispersing for 25 minutes, adding acrylamide, and ultrasonically dispersing for 28 minutes, and then adding N,N'-methylenebisacrylamide, and ultrasonically dispersing for 2 minutes to prepare a polypyrrole-acrylamide mixed solution, and dry-mixing fine aggregate and coarse aggregate for 3 minutes, and then adding silicate cement, steel slag and nickel-iron slag and dry-mixing for 3 minutes to prepare a dry mix;

[0076] 2) Dispersing ammonium persulfate in 24 parts by mass of water, adding the dry mix, stirring for 4 minutes, adding the polypyrrole-acrylamide mixed solution and 24 parts by mass of water, stirring for 4 minutes, injecting into a mold for molding, and then curing at 40° C. for 6 hours, and then transferring to a room temperature environment for curing until the total curing time reaches 28 days, thereby obtaining radiation-proof concrete.

[0077] After testing, the 28-day neutron attenuation coefficient of the radiation-proof concrete in this embodiment is 0.19 cm -1 The compressive strength after 28 days is 54MPa, the dynamic elastic modulus after 28 days is 36GPa, and the shrinkage rate after 28 days is 160μm / m, indicating that it has strong neutron radiation protection ability and high strength.

[0078] Embodiment 5:

[0079] A radiation-proof concrete, the raw material composition of which is shown in the following table:

[0080] Table 5: Raw material composition of a radiation-proof concrete

[0081]

[0082] The preparation method of the above-mentioned radiation-proof concrete is as follows:

[0083] 1) dispersing a polycarboxylate water reducer in 13 parts by mass of water, adding polypyrrole nanocrystals, and ultrasonically dispersing for 25 minutes, adding acrylamide, and ultrasonically dispersing for 20 minutes, and then adding acrylic acid, and ultrasonically dispersing for 4 minutes to prepare a polypyrrole-acrylamide mixed solution, and dry-mixing fine aggregate and coarse aggregate for 3 minutes, and then adding silicate cement, steel slag and nickel-iron slag and dry-mixing for 2 minutes to prepare a dry mix;

[0084] 2) Sodium persulfate was dispersed in 26 parts by mass of water, and then the dry mix was added and stirred for 2 minutes, and then the polypyrrole-acrylamide mixed solution and 26 parts by mass of water were added and stirred for 1 minute, and then injected into a mold for molding, and then placed at 40° C. for curing for 5 hours, and then transferred to a room temperature environment for curing until the total curing time reached 28 days, thereby obtaining radiation-proof concrete.

[0085] After testing, the 28-day neutron attenuation coefficient of the radiation-proof concrete in this embodiment is 0.07 cm-1 The 28-day compressive strength is 52MPa, the 28-day dynamic elastic modulus is 34GPa, and the 28-day shrinkage rate is 145μm / m, indicating that it has strong neutron radiation protection ability and high strength.

[0086] Comparative Example 1:

[0087] A concrete which is completely the same as the radiation-proof concrete in Example 1 except that it does not contain "polypyrrole nanocrystals".

[0088] After testing, the 28-day neutron attenuation coefficient of the concrete in this comparative example is 0.03 cm -1 The 28-day compressive strength is 55MPa, the 28-day dynamic elastic modulus is 35GPa, and the 28-day shrinkage rate is 113μm / m, indicating that the neutron radiation protection ability of concrete will be greatly reduced if polypyrrole nanocrystals are not added.

[0089] Comparative Example 2:

[0090] A concrete, which is completely the same as the radiation-proof concrete in Example 2 except that the amount of acrylamide is adjusted from "8 parts by mass" to "1 part by mass".

[0091] After testing, the 28-day neutron attenuation coefficient of the concrete in this comparative example is 0.01 cm -1 The 28-day compressive strength is 52MPa, the 28-day dynamic elastic modulus is 33GPa, and the 28-day shrinkage rate is 361μm / m, which shows that too low acrylamide dosage will not only greatly reduce the neutron radiation protection ability of concrete, but also cause the shrinkage rate of concrete to increase significantly.

[0092] Comparative Example 3:

[0093] A concrete, which is exactly the same as the radiation-proof concrete in Example 3, except that "steel slag" and other qualities are replaced by "slag (particle size of 10μm to 30μm)" and "nickel-iron slag" and other qualities are replaced by "fly ash (particle size of 10μm to 30μm)".

[0094] After testing, the 28-day neutron attenuation coefficient of the concrete in this comparative example is 0.02 cm -1 The 28-day compressive strength is 48MPa, the 28-day dynamic elastic modulus is 26GPa, and the 28-day shrinkage rate is 205μm / m, which shows that the replacement of steel slag and nickel-iron slag will not only greatly reduce the neutron radiation protection ability of concrete, but also cause the shrinkage rate of concrete to increase significantly.

[0095] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A radiation-proof concrete, characterized in that: The preparation method comprises the following raw materials in parts by weight: Portland cement: 100 parts; Polypyrrole nanocrystals: 0.1 to 1 part; Acrylamide: 3 to 10 parts; Initiator: 0.005 to 0.1 parts; Cross-linking agent: 0.005 to 0.2 parts; Steel slag: 5 to 10 parts; Ferronickel slag: 8 to 20 parts; Fine aggregate: 160 to 200 parts; Coarse aggregate: 270-330 parts; Water reducing agent: 1 to 3.5 parts; Water: 40 to 65 parts.

2. The radiation-proof concrete according to claim 1, characterized in that: The particle size of the polypyrrole nanocrystal is 20nm-100nm.

3. The radiation-proof concrete according to claim 1 or 2, characterized in that: The initiator is at least one of ammonium persulfate and sodium persulfate.

4. The radiation-proof concrete according to claim 1 or 2, characterized in that: The cross-linking agent is at least one of N,N'-methylenebisacrylamide, sodium vinyl sulfonate and acrylic acid.

5. The radiation-proof concrete according to claim 1 or 2, characterized in that: The particle size of the steel slag is 10 μm to 20 μm.

6. The radiation-proof concrete according to claim 1 or 2, characterized in that: The particle size of the nickel-iron slag is 15 μm to 40 μm.

7. The radiation-proof concrete according to claim 1 or 2, characterized in that: The fine aggregate is at least one of natural river sand and machine-made sand, and has a particle size of 0.075 mm to 4.75 mm.

8. The radiation-proof concrete according to claim 1 or 2, characterized in that: The coarse aggregate is at least one of granite, diabase and limestone, and has a particle size of 4.75 mm to 26 mm.

9. A method for preparing radiation-proof concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) dispersing polypyrrole nanocrystals, acrylamide, a crosslinking agent and a water reducing agent in a portion of water to prepare a polypyrrole-acrylamide mixed solution, and mixing silicate cement, steel slag, nickel-iron slag, fine aggregate and coarse aggregate to prepare a dry mix; 2) Disperse the dry mix and the initiator in a portion of the water, add the polypyrrole-acrylamide mixed solution and the remaining water, mix well, and then perform molding and curing to obtain radiation-proof concrete.

10. A building material, characterized in that: The invention comprises the radiation-proof concrete according to any one of claims 1 to 8.